Comparative study of CTX-II, Zn2+, and Ca2+ from the urine for knee osteoarthritis patients and healthy individuals. Issue 32 (August 2017) - Xin, Linwei; Wu, Zhihai; Qu, Quanli; Wang, Ruiying; Tang, Jichun; Chen, Lei
Abstract : Abstract: The aim of the study was to explore the relationship between the concentration of C-telopeptide fragments of type II collagen (CTX-II), Zn 2+, and Ca 2+ in urine and knee osteoarthritis (KOA). Eighty-two patients with KOA and 20 healthy volunteers were enrolled. Anteroposterior and lateral position x-rays of knee joints were collected. The images were classified according to Kellgren-Lawrence radiographic grading criterion. The patients were divided into group grade I, group grade II, group grade III, and grade IV. The concentration of CTX-II in the urine was detected by enzyme-linked immunosorbent assay. The concentration of Zn 2+ and Ca 2+ in urine was detected by inductively coupled plasma atomic emission spectrometry. Compared with the healthy individuals, the concentration of CTX-II was significantly higher in KOA patients. The concentration of CTX-II in KOA patients from high to low was as follows: group IV, group III, group II, and group I. There was no significant difference between group I and healthy individuals. The concentration of Zn 2+ and Ca 2+ in urine of KOA patients was higher than that in healthy individuals. There was no difference in each KOA group. The concentration of CTX-II is instrumental to diagnose the progress of KOA. The concentration of Zn 2+ and Ca 2+ in urine is helpful for early diagnosis of KOA.